Foreign Currency Risk Measurement Methods and Application of them in Lithuania - Staškevičius, Juozapas Audvydas; Bagdonienė, Renata (Ekonomika, 2000)
Risk measurement plays an important role in a general risk management cycle of a company. It is impossible to control a risk and determine potential losses without a performance of quantitative risk estimation.The article covers the analysis of a contemporary foreign currency risk measurement methods, emphasizes it, strengths and weaknesses. The following methods of a Value at Risk concept are assessed as the most progressive ones: Variance/covariance. Historical simulation and Monte Carlo simulation. Variance/covariance method is suggested for Lithuanian companies to measure their foreign currency risk. The research undertaken proves that this method matches actual changes of the market.